Promoting Teacher Autonomy through Educational Innovation - Usma, Jaime; Frodden, Cristina (Íkala, Revista de Lenguaje y Cultura, 2003)
In this paper, a teacher-researcher and his advisor report on an action research project aimed at developing teacher autonomy through collaborative work on the redesign and implementation of a new English syllabus in a high school in Medellín. Educational innovation, collaborative work, and autonomy development emerged as the main themes related to changing teacher and school practices. Teacher autonomy development requires certain conditions, but the process of change can create these conditions. With this paper we aim at a better understanding of and a discussion on the field of teacher autonomy, especially about the conditions required to begin educational innovations in our institutions, and how these conditions are related to teacher autonomy. Received: 17-07-03 / Accepted: 19-08-03. How to reference this article: Usma, J. & Frodden, C. (2003). Promoting Teacher Autonomy through Educational Innovation. Íkala. 8(1), pp. 101 – 132